EFEKTIVITAS PROGRAM PELAKSANAAN PELATIHAN TENAGA KERJA DI BALAI BESAR PELATIHAN VOKASI DAN PRODUKTIVITAS (BBPVP) DI KOTA SERANG - Juliana; Titi Stiawati (NIAGARA Scientific Journal, 2023)
Unemployment is one of the main problems in Indonesia. The problem of unemployment is closely related to economic growth. Unemployment as a problem in development in the country requires efforts to overcome it. One of the efforts to reduce unemployment is the need for manpower training, through training it is hoped that the quality of human resources in the country will increase and meet the criteria needed in the labor market. Many government agencies have attempted employment training, namely the Vocational and Productivity Training Center in Serang City. This study uses the Center for Vocational Training and Productivity Serang City as one of the research objects with the aim of knowing the effectiveness of the implementation of workforce training programs. This research uses a qualitative approach with the type of data analysis collected through interviews. The theory of the dimensions of Effectiveness Nazir (2005) which contains four dimensions of effectiveness, namely: Accuracy of program targets, Program socialization, Program objectives, and Program monitoring. The research results obtained are effective for the Vocational and Productivity Training Center of Serang City in the workforce training program, but it is necessary to channel the workforce directly to companies from training participants and it is necessary to socialize job training programs